Additive schemes based domain decomposition algorithm for solving singularly perturbed parabolic reaction-diffusion systems - Aakansha; Singh J.; Kumar S. (My University, 2025)
In this paper, we examine a 1D parabolic coupled system of singularly perturbed reaction-diffusion problems in which perturbation parameters can be of distinct magnitude. To solve this system numerically we develop additive (or splitting) schemes based domain decomposition algorithm of Schwarz waveform relaxation type. On each subdomain we consider two additive schemes on a uniform mesh in time and the standard central difference scheme on a uniform mesh in space. We provide convergence analysis of the algorithm using some auxiliary problems and the algorithm is shown to be uniformly convergent. The additive schemes make the computation more efficient as they decouple the components of the approximate solution at each time level. Numerical results for two test problems are given in support of the theoretical convergence result and as well as to illustrate the efficiency of the additive schemes. © 2021, SBMAC - Sociedade Brasileira de Matemática Aplicada e Computacional.